2016
DOI: 10.1111/cen.13249
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life decrements in men with prostate cancer undergoing androgen deprivation therapy

Abstract: Within 12 months, ADT is associated with clinically significant decreased QoL, particularly physical and sexual aspects, independent of the confounding effects of a cancer diagnosis or radiotherapy. As QoL is a crucial aspect of prostate cancer treatment, addressing hot flushes, sexual dysfunction and exercise may potentially improve outcomes for men undergoing ADT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 28 publications
0
40
2
1
Order By: Relevance
“…There were no significant differences in mental component of QoL. During ADT, AMS score increased reflecting worse QoL, which was related to an increase in hot flushes (9). Two years after cessation of ADT, AMS was also no longer different to controls likely related to an improvement in hot flushes (MAD: 3.3 (−0.8 to 7.6), P = 0.12).…”
Section: Total Testosteronementioning
confidence: 81%
See 2 more Smart Citations
“…There were no significant differences in mental component of QoL. During ADT, AMS score increased reflecting worse QoL, which was related to an increase in hot flushes (9). Two years after cessation of ADT, AMS was also no longer different to controls likely related to an improvement in hot flushes (MAD: 3.3 (−0.8 to 7.6), P = 0.12).…”
Section: Total Testosteronementioning
confidence: 81%
“…QoL was measured by the 12-item Short-Form QoL Survey, version 2 (SF-12), which generates a physical and mental component score and the Aging Males' Symptoms (AMS) Scale as previously described (9,17).…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…They are often mild and abate, but may persist and be severe enough to warrant pharmacotherapy (Karling et al 1994, Sharifi et al 2005, Jones et al 2012. Hot flushes may interfere with sleep and, along with other side effects of ADT, reduce quality of life (Cheung et al 2016). Men undergoing ADT generally experience loss of libido, erectile dysfunction and reduced sexual activity (Grossmann & Zajac 2011).…”
Section: Constitutional Vasomotor and Sexual Symptomsmentioning
confidence: 99%
“…Despite the survival improvement , ADT also negatively influences bone, metabolic, cardiovascular, sexual and cognitive health as well as body composition, fatigue and vasomotor flushing . These side effects are detrimental for the patient's health and quality of life , therefore, it is imperative to mitigate them through the introduction of treatments aimed at reducing them. Evidence‐based guidelines have been drawn up to reduce the impact of ADT‐induced side effects , but a European study showed that these guidelines are not sufficiently applied in clinical routine .…”
Section: Introductionmentioning
confidence: 99%